2008
DOI: 10.1089/thy.2008.0044
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Clinical Features of Thyroid-Associated Ophthalmopathy in Multiethnic Malaysian Patients with Graves' Disease

Abstract: TAO has relatively high prevalence rate (34.7%) in three populations of Asian patients with GD. This is similar to that reported for Caucasian patients with GD. As in Caucasian patients, smoking increases the risk of TAO. In the Asian populations we studied, exophthalmos was the most common eye sign. However, lower lid retraction was also common and present in 60% of cases with other signs of TAO. In Chinese, Malay, and Indian Asians with GD, lower lid retraction should be a diagnostic criterion for TAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 22 publications
10
48
1
Order By: Relevance
“…Moreover, Asians appear to have less severe manifestations, with milder features of orbital edema, proptosis and muscle restriction (46). A cross sectional study of Malay, Chinese and Indian GO patients with Graves' disease in Malaysia showed that the prevalence of GO ranged from 35.1% to 40.0% in the three populations, similar to the prevalence observed in Caucasians (16). A similar frequency of GO of 33% has been documented in juvenile patients with Graves' (58).…”
Section: Clinical Presentationsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, Asians appear to have less severe manifestations, with milder features of orbital edema, proptosis and muscle restriction (46). A cross sectional study of Malay, Chinese and Indian GO patients with Graves' disease in Malaysia showed that the prevalence of GO ranged from 35.1% to 40.0% in the three populations, similar to the prevalence observed in Caucasians (16). A similar frequency of GO of 33% has been documented in juvenile patients with Graves' (58).…”
Section: Clinical Presentationsupporting
confidence: 57%
“…Class I (Only signs): Upper lid retraction, staring and eyelid lag are observed in 35-53% of patients with Graves' disease (16) and in 90-98% of Caucasian patients (19,20) and 57% of Japanese patients (29) with GO.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In contrast, the prevalence of GO among 167 consecutive multiethnic Malaysian patients with Graves' disease was 34.5%, no different from that in Caucasians [9]. Exo phthalmos and lower lid retraction were the most common eye signs in this population.…”
Section: Are There Ethnic Differences?mentioning
confidence: 54%
“…The eye signs correlated only modestly with calsequestrin and collagen XIII antibodies. In contrast to patients with Graves' disease, where cigarette smoking is shown to be a major risk factor for ophthalmopathy Lim et al 2008;Nassar et al 2009), there was no relationship between smoking status and eye abnormalities in patients with Hashimoto's thyroiditis (Tjiang et al 2010). Muller et al found that among women with subclinical hypothyroidism, smokers had higher serum TSH levels, higher serum ratio of T3 to free T4, and also higher cholesterol and low-density lipoprotein cholesterol concentrations than non-smokers (Muller et al 1995).…”
Section: Smoking and Autoimmune Thyroid Diseases (Aitd)mentioning
confidence: 84%